Transanal intersphincteric under direct view in the jackknife position combined with laparoscopic total mesorectal excision for treating ultra-low rectal cancer - Zhong, Guobin; Chen, Zhiyu; Li, Zhenfeng; Zhao, Bin; Deng, Junhui (Frontiers in Surgery, 2024)
AimTo investigate the effect and clinical advantage of transanal intersphincteric (ISR) under direct view in the jackknife position combined with laparoscopic total mesorectal excision (TME) for treating ultra-low rectal cancer. Additionally, the feasibility of this surgical technique was evaluated.MethodThis was a retrospective, single-center, single-arm pilot study. Ten patients with ultra-low rectal cancer underwent treatment by the same surgical team for direct view transanal ISR combined with laparoscopic TME in the Department of Anorectal Surgery, Huizhou Central People's Hospital between January 2021 and June 2021. The relevant clinical data were collected and analyzed.ResultsAll the patients underwent complete mesenteric resection without conversion to laparotomy. The circumferential and distal resection margins (CRM and DRM) were negative. The mean distance between the lower margin of the tumor and the anal margin was 2.8 ± 0.8 cm, and the mean margin of distal resection was 1.2 ± 0.2 cm. TNM pathological stages I, II, III, and IV were observed in 6, 2, 2, and 0 cases, respectively. The median follow-up period was 15 months (interquartile range, 8 months). The mean Wexner and Low Anterior Resection Syndrome scores at 12 months after ileostomy were 8.1 ± 2.1 and 22.4 ± 5.7, respectively.ConclusionTransanal ISR under direct view in the jackknife position combined with laparoscopic TME is safe and feasible for the treatment of ultralow rectal cancer.